iPractice: Piloting the Effectiveness of a Tablet-Based Home Practice Program in Aphasia Treatment - Kurland, Jacquie; Wilkins, Abigail R.; Stokes, Polly (Seminars in Speech and Language, 2014)
The current study investigated the effectiveness of a home practice program based on the iPad (Apple Inc., Cupertino, CA), implemented after 2 weeks of intensive language therapy, for maintaining and augmenting treatment gains in people with chronic poststroke aphasia. Five of eight original participants completed the 6-month home practice program in which they autonomously practiced retrieving words for objects and actions. Half of these words had been trained and half were untrained during therapy. Practice included tasks such as naming to confrontation, repeating from a video model, and picture/word matching presented on an iPad. All participants maintained advances made on words trained during the intensive treatment and additionally were able to learn new words by practicing daily over a 6-month period. The iPad and other tablet devices have great potential for personalized home practice to maintain and augment traditional aphasia rehabilitation. It appears that motivation to use the technology and adequate training are more important factors than age, aphasia type or severity, or prior experience with computers.
Keywords: Aphasia; home practice; treatment; technology; iPad